STRATEGI KOMISI PEMILIHAN UMUM (KPU) KABUPATEN BANYUMAS DALAM MENINGKATKAN PARTISIPASI PUBLIK PEMILIH PEMULA PADA PILKADA 2024 - Oktavia Ramadhani; Zaula Rizqi Atika; Indah Ayu Permana Pribadi; Ariesta Amanda; Chamid Sutikno (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2026)
Voter participation in the Banyumas Regency Regional Election declined from 74.37% in 2018 to 68.9% in 2024, with a more pronounced decline among first-time voters totaling 134,689 individuals or approximately 10% of registered voters. This study analyzes the strategies of the Banyumas Regency General Election Commission (KPU) in increasing first-time voter participation in the 2024 regional election, covering strategy formulation, implementation, and evaluation. A descriptive qualitative method was employed through in-depth interviews, observation, and document analysis, grounded in David's (2016) strategic management theory and the New Public Service paradigm (Denhardt & Denhardt, 2015). The results show that KPU formulated six strategies, including collaboration with research institutions, voter segmentation, partnerships with content creators, and culture-based programs such as the Election Kirab featuring traditional performing arts of ebeg and gamelan. Implementation achieved positive outputs: participant understanding improved from 60% to 85%, and KPU's social media followers reached 20,000 — the largest among regency-level KPUs in Central Java. However, actual participation declined. The most dominant factor was the presence of a single candidate pair, which reduced first-time voters' external political efficacy, followed by voter fatigue, e-ID card barriers, and voter mobility. Stronger administrative early warning systems, outcome-based evaluation, and sustainable participatory ecosystems are needed.